2013
DOI: 10.5664/jcsm.2928
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea (OSA) in Preadolescent Girls is Associated with Delayed Breast Development Compared to Girls without OSA

Abstract: The Tucson Children's Assessment of Sleep Apnea study (TuCASA) is a prospective cohort study of 6-to 11-year-old children with and without OSA followed over a 4-to 5-year period to investigate the predictors and neurocognitive and physiological sequelae of OSA. As pubertal stage was one of the measures obtained at follow-up, this study represents a unique opportunity to examine the effect of OSA on the pace of pubertal development in otherwise healthy children. Based Study Objective: Adults with obstructive sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In addition to the effect of circadian dysregulation, it should be kept in mind that shift work-related alterations in other daily functions, particularly food intake and sleep, may indirectly impact female reproduction. Thus, obesity, which is often associated with shift work, has a strong impact on reproductive performance ( 180 ) and sleep disturbance in prepubertal girls can alter estradiol-dependent pubertal development ( 181 ).…”
Section: Shift-work Consequences On Reproductive Cycles and Fertilitymentioning
confidence: 99%
“…In addition to the effect of circadian dysregulation, it should be kept in mind that shift work-related alterations in other daily functions, particularly food intake and sleep, may indirectly impact female reproduction. Thus, obesity, which is often associated with shift work, has a strong impact on reproductive performance ( 180 ) and sleep disturbance in prepubertal girls can alter estradiol-dependent pubertal development ( 181 ).…”
Section: Shift-work Consequences On Reproductive Cycles and Fertilitymentioning
confidence: 99%
“…Both laboratory and field studies have demonstrated that hypoxia can affect specific genes along the brain-pituitary-gonad axis, disrupt the synthesis and balance of sex hormones and lead to reproductive impairments and sex alteration in several fish species 4 5 6 . Notably, hypoxia can also cause similar endocrine disruption and reproductive impairments in rhesus monkeys and humans living at high altitudes 7 8 9 , and men suffering from hypoxia as a consequence of sleep apnoea exhibit lower levels of male and female sex hormones as well as reduced sex drive 10 11 12 , showing that hypoxic responses are highly conserved in vertebrates.…”
mentioning
confidence: 99%
“…Hypoxia suppression of EGF signaling is conserved in other organisms (Deygas et al, 2018;Maxeiner et al, 2019), and altered expression of EGFR signaling components has been reported both in human populations living in high altitudes (Jha et al, 2016) and in Drosophila populations which have undergone multiple generations of selection for hypoxia tolerance (Zhou et al, 2008). Also, hypoxia can modulate steroidogenesis and steroid functions in many animals (Bera et al, 2020;Oyedokun et al, 2023;Wang et al, 2008;Yao et al, 2021), and diseases that can result in reduced systemic oxygen levels in humans -such as chronic obstructive pulmonary disease, sleep apnea or asthma -can impact steroid-induced development and sexual maturation (Drosdzol et al, 2007;Gaudino et al, 2021;Shaw et al, 2013). Thus, the mechanisms that we describe here in Drosophila may reflect more general mechanisms by which low oxygen can affect animal development.…”
Section: Discussionmentioning
confidence: 99%